2022
DOI: 10.1016/j.jad.2021.10.001
|View full text |Cite|
|
Sign up to set email alerts
|

Curiosity helps: Growth in need for cognition bidirectionally predicts future reduction in anxiety and depression symptoms across 10 years

Abstract: Introduction: Decreased motivational tendency to seek out, engage in, and enjoy investing in complex cognitive processes in a sustained manner (need for cognition; NFC) may be a predictor and consequence of heightened anxiety and depression symptoms (ADS).However, the majority of investigations on this topic have been cross-sectional, which hinders causal inferences. Methods: The current study thus determined the within-person relations between NFC and ADS by using random intercept cross-lagged panel model (RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 134 publications
(141 reference statements)
0
6
0
Order By: Relevance
“…Although it is less clear why people would be more curious about others who agree with them than others than disagree with them, people who are more responsive to intrinsically rewarding stimuli may be more curious. Curiosity in turn is associated with mental health 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is less clear why people would be more curious about others who agree with them than others than disagree with them, people who are more responsive to intrinsically rewarding stimuli may be more curious. Curiosity in turn is associated with mental health 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Without this combination of expected effects, observed effects would appear to be spurious and conclusions of causality premature. We Sorjonen, Nilsonne, et al, 2024; have previously used this type of triangulation and challenged conclusions in studies using RI-CLPM and claiming effects of need of cognition on anxiety and depression symptoms (Zainal & Newman, 2022), of income on self-esteem (Bleidorn et al, 2023), of curiosity on creativity and vice versa (Ma & Wei, 2023), and of self-esteem on eating pathology and vice versa (Beckers et al, 2023). We recommend researchers to use similar triangulations to scrutinize findings from analyses of observational data.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding perfectionism, a study conducted among athletes demonstrated that both self-oriented and socially prescribed performance perfectionism were correlated with burnout [ 25 ]. Curiosity has been identified as a protective factor against anxiety, depression, and suicidal ideation in several studies [ 26 , 27 ]. Additionally, research has linked decision-making [ 28 ], innovation [ 29 ] and leadership [ 30 ] to the development of various job-related mental disorders.…”
Section: Discussionmentioning
confidence: 99%